Pemanfaatan Moda Gerobak Motor, Sebagai Sarana Peningkatan Produktivitas Dan Layanan Laundry Keliling Di Green Laundry Jombang (TEKAD : Teknik Mengabdi, 2025)
Green Laundry is a small business unit offering washing and ironing services based on weight (kilograms) in Jombang Regency. This business provides affordable washing and ironing services compared to existing laundry services while maintaining high-quality standards. With the slogan, "Making your life easier," Green Laundry consistently strives to deliver the best services to meet customer needs. Since its establishment, this business has contributed to providing job opportunities, especially for underprivileged women and widows who urgently need work to support their families. Thus, this business is not solely profit-oriented but also carries a social mission. To accommodate this purpose, Green Laundry is required to improve its productivity to enable the hiring of more workers. Therefore, innovation in service improvement is necessary. One of the initiatives to be implemented is introducing a Full Delivery Service to facilitate customer access to Green Laundry’s services. To support the implementation of the Full Delivery Service, the PKM team has provided a motorized cart to function as a mobile booth. This motorized cart serves as a means of collecting laundry from customers in a scheduled and rotational manner across various residential areas and villages. This approach has successfully increased Green Laundry's productivity, evidenced by the growth in transaction numbers, total laundry weight processed, and revenue. In the future, this initiative is expected to create additional job opportunities for those in need.